The relative influence of cross‐seasonal and local weather effects on the breeding success of a migratory songbird. Issue 7 (27th April 2022) - de Zwaan, Devin R.; Drake, Anna; Camfield, Alaine F.; MacDonald, Elizabeth C.; Martin, Kathy
Abstract: In seasonal environments, fluctuating early‐season weather conditions and short breeding windows limit reproductive opportunities such that breeding earlier or later than the optimum may be particularly costly. Given the risk of early‐season energy limitations, time‐ and energy‐based carry‐over effects stemming from environmental conditions across the annual cycle may have pronounced consequences for breeding phenology and fitness. Generally, when and where environmental conditions are most influential are poorly understood, limiting our ability to predict the future of climate‐sensitive populations. For an alpine‐breeding, migratory population of horned lark Eremophila alpestris in northern British Columbia, Canada (54.8°N), we assessed how weather conditions across the annual cycle influenced clutch initiation date and offspring development. We also addressed how cross‐seasonal effects on breeding parameters combine to influence reproductive fitness. With 12 years of breeding data and 3 years of migration data, we used a sliding window approach to identify points during the annual cycle when weather events most influenced breeding phenology and offspring development. Consequences for breeding success were assessed using nest survival simulations. Average clutch initiation date varied up to 11 days among years but did not advance from 2003 to 2019. Warmer temperatures at stopover and breeding sites advanced clutch initiation, but winter conditions had no effect. Sub‐zero stopover temperatures carried over to prolong offspring development independent of clutch initiation date, potentially indicating energy‐based carry‐over effects acting on parental investment. Nest survival decreased with both later clutch initiation and prolonged offspring development such that females nesting earlier and fledging offspring at a younger age were up to 45% more likely to reproduce successfully. We demonstrate that stronger carry‐over effects originated from environmental conditions closer to the breeding site in time and space, as well as the potential for energy‐based mechanisms to link pre‐breeding conditions to reproductive fitness. We also highlight the importance of extended stopovers for songbirds breeding in seasonal environments, particularly given that climatic conditions are becoming increasingly decoupled across stages of the annual cycle. Understanding the cross‐seasonal mechanisms shaping breeding decisions in stochastic environments allows for more accurate predictions of population‐level responses to climate change. Abstract : Suboptimal weather at the stopover and breeding site delay clutch initiation and prolong offspring development, which, in turn, combine synergistically to drastically reduce nest success in an alpine breeding songbird. Photo credit: David Bell. Résumé: Les variations saisonnières de l'environnement, notamment due aux conditions climatiques changeantes en début de saison ainsi que la réduction de la période propice à l'accouplement contraint fortement les possibilités de reproduction. Dans ces conditions, s'accoupler avant ou après le moment optimal peut s'avérer particulièrement coûteux. Les effets de report (temporels et énergétiques) causés par ces variations environnementales peuvent avoir des conséquences notables sur la phénologie de la reproduction, et ultimement sur la valeur sélective des individus. Où et quand les effets des conditions environnementales sont le plus critiques reste encore méconnu, limitant notre capacité à prédire le futur des populations sensibles aux variations climatiques. Ici, nous avons évalué comment des conditions climatiques au cours de l'année influencent la date de ponte et le développement des oisillons dans une population migratrice d'Alouette hausse‐col Eremophila alpestris se reproduisant en milieux alpin. Nous tirons profit de données issues de 12 ans de suivit de la reproduction et de 3 ans de suivit migratoire, et utilisons une approche dite de 'sliding window' pour identifier les moments du cycle annuel pour lequel le climat a eu le plus d'influence sur la phénologie de la reproduction et le développement des oisillons. La date moyenne de ponte s'avère variable d'une année à l'autre (certaine différence allant jusqu'à 11 jours), mais ne se décale pas sur la période de 2003 à 2019. Nos résultats montrent que des conditions climatiques plus chaudes lors des haltes migratoires ainsi que sur les sites de reproductions rendent la date de ponte plus précoces. Des températures négatives lors des haltes migratoires aussi ont pour conséquences un temps de développement des oisillons plus long, et ceci indépendamment de la date de ponte. Cela suggère des effets de report, notamment énergétique, affectant l'investissement des parents. Nos résultats montrent que la survie au nid diminue lorsque la date de ponte est plus tardive ou que le temps de développement des oisillons est rallongé. De cette manière, les femelles commençants la nidification plus tôt et pour qui les oisillons quittent le nid plus tôt ont 45% plus de chance de se reproduire avec succès. Nous démontrons que des conditions environnementales proche du site de reproduction (que ce soit dans le temps ou dans l'espace) cause un fort effet de report, et suggérons un possible mécanisme reliant les conditions climatiques pré‐reproductives au succès reproducteur. De plus, nous mettons en lumière l'importance des haltes migratoires prolongées pour la reproduction des passereaux en environnement saisonnier, particulièrement du fait que les conditions climatiques sont de plus en plus découplées au cours des les étapes du cycle annuel. Une meilleure compréhension des mécanismes inter‐saisonniers influençant les décisions de reproduction en environnement stochastique permettrait de mieux prédire les réponses des populations aux changements climatiques.